The correlation between plasma homocysteine and malondialdehyde levels in preeclampsia - Tug, N; Celik, H; Cikim, G; Ozcelik, O; Ayar, A (Maghira & Maas Publications, 2003)
OBJECTIVE: To investigate the possible correlation between plasma malondialdehyde and homocysteine levels of preeclamptic patients. DESIGN: Venous blood samples of 20 preeclamptics and 20 healthy pregnant controls were collected. Plasma malondialdehyde and homocysteine concentrations were measured and the correlation between them was investigated. Mann Whitney U test and Spearman correlation analysis were used for statistical analysis. SETTING: University of Firat, Medical School. RESULTS: Plasma malondialdehyde and homocysteine concentrations were higher in preeclamptic patients (p<0.05) and a positive correlation between these parameters was found (r:0.77, p<0.01, n:20). CONCLUSION: Our results may put forward some new strategies in the research of etiopathogenesis and treatment of preeclampsia.
Keywords: malondialdehyde; homocysteine; preeclampsia